Ethnomathematics of small border islands: Geometric concepts in Koli leaf weaving on Letti Island - Dahoklory, Andy Sunder Keer; Sugiarto, Sigit; Rupilele, Karolina (Indonesian Journal of Science and Mathematics Education, 2025)
Ethnomathematics connects mathematical concepts with cultural practices, making learning more contextual and meaningful. However, studies in small border islands remain limited, despite their rich cultural heritage. One example is Koli leaf weaving on Letti Island, which reflects mathematical ideas in daily life. This study aims to conduct an ethnomathematical study of Koli leaf-woven objects on small border islands using a qualitative ethnographic approach that includes literature review, observation, interviews, and documentation. The collected data is analyzed using content analysis, thematic analysis, and pattern recognition. The findings reveal that Koli leaf weaving involves mathematical concepts, including plane shapes (triangles, circles, hexagons) and solid shapes (hexagonal prisms, cylinders). These findings imply that local cultural artifacts can serve as contextual learning resources in mathematics and science education. The geometric patterns of Koli leaf weaving can be used in geometry lessons to strengthen students’ mathematical literacy, critical thinking, and appreciation of local culture. This research also has implications for the preservation of local knowledge and the development of culture-based mathematics education on small border islands.